2015
DOI: 10.1111/jan.12764
|View full text |Cite
|
Sign up to set email alerts
|

Patients' perceptions of transgressive behaviour in care relationships with nurses: a qualitative study

Abstract: Patients adjust their behaviour based on what they experience in care relationships with nurses or the hospital care. It is crucial that patients feel free to discuss their assumptions or untoward needs and nurses learn to understand and reflect on those experiences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Arguably, patients adjust their behaviour based on what they experience in care relationships with nurses or the hospital care (Mosadeghrad, 2012; Vandecasteele et al , 2015). Further evidence from Ghana indicates that verbal abuse is more problematic in public than private healthcare facilities (Yakong et al , 2010; Mannava et al , 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Arguably, patients adjust their behaviour based on what they experience in care relationships with nurses or the hospital care (Mosadeghrad, 2012; Vandecasteele et al , 2015). Further evidence from Ghana indicates that verbal abuse is more problematic in public than private healthcare facilities (Yakong et al , 2010; Mannava et al , 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Besides nurses wanting to maintain control over care, it also seems plausible that nurses find it difficult taking into consideration the patient's perspective. Qualitative research by Vandecasteele et al [35] focussing on transgressive behaviour in care relationships found that nurses generally perceive the relationship with the patient from their own point of view, and do not necessarily insert the individual patient perspective in their interaction with patients. Difficulties experienced by the nurses for incorporating an individualised approach during care were also observed in a multi-site ethnography study by van Belle et al [36] The study demonstrated that although some nurses achieve to do so, providing individualised care in hospitals remains difficult, as most nurses are not able to incorporate the physical, relational and physical elements of care [36].…”
Section: Comparing Patients' and Nurses' Perceptions Of Individualised Carementioning
confidence: 99%
“…A shared understanding towards the support and provision of individualised care and being sensitive towards the patient perspective could generate more effective nursing care that takes into account the individuality of the patient [37,38] T A B L E 5 Multilevel results for the Dutch and Flemish patients nurses think that the care is individualised per se or if they are a priori convinced that the care they provide already incorporates individual patient preferences, needs and values, changing existing interactions between patients and nurses will be challenging. Reflecting on one's own perceptions of individualised care, how these perceptions emerge or where they emanate from could be a starting point and essential in creating awareness among nurses to provide care that is more individualised and incorporates the patients' perspective [3,35]. Self-awareness will contribute to professional growth of nurses and will aid in becoming more understanding towards patients, establishing an effective nurse-patient relationship, and taking a more critical stance towards the care provided [39][40][41].…”
Section: Comparing Patients' and Nurses' Perceptions Of Individualised Carementioning
confidence: 99%